2022
DOI: 10.1155/2022/4914792
|View full text |Cite
|
Sign up to set email alerts
|

A Comprehensive Analysis of Teacher’s Professional Identity in Physical Education Undergraduates Based on Artificial Intelligence

Abstract: Physical education (PE) teachers are instrumental in advancing China’s curriculum reform and promoting the wellness of adolescents, and the professional identity of these instructors represents the jumping-off point and drive of the occupation. This paper employed the implicit association test (IAT) based on the neural network model and the questionnaire survey method to compare the implicit and explicit stereotypes of teachers’ occupational commitment from the perspectives of college students majoring in PE. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…Girard et al [33] identifies a connection between students' motivational factors and the motivational environment they perceive. Xu and Luo [34] reveals both overt and covert stereotypes about physical education teachers' professional dedication, indicating shifts in motivational structures and new influencing elements.…”
Section: Discussionmentioning
confidence: 99%
“…Girard et al [33] identifies a connection between students' motivational factors and the motivational environment they perceive. Xu and Luo [34] reveals both overt and covert stereotypes about physical education teachers' professional dedication, indicating shifts in motivational structures and new influencing elements.…”
Section: Discussionmentioning
confidence: 99%
“…It is true that there are fundamental differences in the physiology of men and women, including physical strength and human emotions for example, men generally have greater strength, while women have a stronger ability to empathize with others [7]. It demonstrated that even for graduates from same major, men tend to default having stronger abilities, especially in physical work, while women are defaulted to being less capable, and are forced to change job functions.…”
Section: Physical Differencesmentioning
confidence: 99%